The Social Welfare System in Bata Company Towns (1920s–1950s): Between Transnational Vision and Local Settings. (April 2023) - Balaban, Milan; Perutka, Lukáš; Paye, Simon; Savić, Dalibor; Herman, Jan
Abstract: In the early twentieth century, the Bata company became one of the largest shoe manufacturers in the world, and an emblematic icon of family capitalism. This paper presents an overview of the social welfare system developed by the firm, first in its hometown of Zlín (Moravia) and then in more than thirty company towns founded in Czechoslovakia, Europe, and other continents from the 1920s to the 1950s. It shows how the initial model provided by the city of Zlín took different forms after being exported to other settlements, and aims to identify the causes of this divergence. Following a transnational perspective, this research contributes to a better understanding of how policies, models, and practices transferred around the world by multinational companies can be reshaped according to national and local contexts.